Impact of biopsychosocial factors on psychiatric training in Japan and overseas: Are psychiatrists oriented to mind, brain, or sociocultural issues? - Kato, Takahiro A. (Psychiatry Clin Neurosci, 2010)
AIM: To clarify the impact of biopsychosocial factors on psychiatric training under the new and traditional postgraduate medical education system in Japan and to compare them with young psychiatrists from other countries. METHODS: Psychiatric residents and early-career psychiatrists were recruited in Japan and other countries. Using mail-based and web-based self-administered questionnaires, we evaluated participants' demographic information, motivation to become psychiatrists, interest and commitment to various aspects of psychiatry, and reactions to a case vignette, focusing on biopsychosocial factors. RESULTS: A total of 137 responses, 81 from Japan and 56 from other countries, were collected. Before starting psychiatric training, Japanese participants showed a strong interest in ‘mind’ and less interest in ‘brain’ and ‘environmental factors’, while the interest in ‘brain’ and ‘environmental factors’ is presently as high as that in ‘mind.’ Japanese participants reported less commitment to their training toward ICD/DSM-based diagnosis, interview, pharmacotherapy, psychosocial treatment and epidemiology, compared with participants from other countries. In particular, Japanese participants showed less commitment to their training in suicide prevention, despite their perception of its high importance due to a high suicide rate in Japan. Suicide risk of a case vignette proved to be differently assessed according to participants' commitment levels to each aspect of psychiatry. CONCLUSION: Our results suggest that young psychiatrists' attitudes concerning the biopsychosocial model generally become well-balanced with psychiatric training, however sociocultural factors do not seem to be well represented in the Japanese psychiatric training system. Additional training on sociocultural issues, such as suicide in Japan, should be considered.